Analisis Kesesuaian Suhu Penyimpanan Bahan Makanan Segar dan Kering terhadap Standar Keamanan Pangan di Rumah Sakit X - Umu Latifatul Jannah; Amalia Rahma (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to analyze the compliance of storage temperatures for fresh and dry food ingredients with food safety standards at Hospital X. The research used a descriptive qualitative–quantitative design with a cross-sectional approach. Data were collected through direct observation, interviews, and documentation at the hospital’s nutrition installation. The results showed that the storage temperature for dry food ingredients ranged from 20°C in the morning to 21.6°C in the afternoon, with an average storage duration of ≤ 1 week. Meanwhile, fresh food ingredients were stored according to their types: staple foods and vegetables in chillers at 8.6°C–9°C, animal-based foods in freezers at -10°C to -9.8°C, plant-based foods and fruits in chillers at 8.6°C–9°C, and seasonings on racks at 20°C–21.6°C. All food materials were stored for no more than one week, as procurement was conducted weekly based on patient numbers and menu cycles. The findings indicate that all storage temperatures complied with the food safety standards set by the Indonesian Ministry of Health and BPOM. Therefore, the food storage system at Hospital X is considered effective, hygienic, and compliant with hospital food safety regulations.